Improving the Students' Data Management Skills through Flipped Classroom - Monique Malabayabas; Cristina E Malabayabas; Narciza M Paz (Research Synergy Foundation, 2025)
The Philippines continues to face educational challenges, as reflected in the 2018 PISA results, which show low performance in reading, science, and mathematics. Limited resources, large class sizes, and high student–teacher ratios contribute to students’ disengagement, particularly in mathematics. To address this issue, the study examined the effectiveness of the flipped classroom approach, a strategy that promotes active student participation in improving college students’ data management skills in mathematics. Using a quantitative pre-experimental design, 27 students completed pretest and posttest assessments, which were analyzed using means, standard deviations, and paired t-tests. Results revealed significant improvement in posttest scores, indicating that the flipped classroom enhances engagement and academic performance in data management. Although limited by a small sample size and narrow focus, the study provides evidence that the flipped classroom can be an effective solution to improve mathematics learning in resource-constrained educational contexts.